Prevalence, type and concentration of human enterovirus and parechovirus in cerebrospinal fluid samples of pediatric patients over a 10-year period: a retrospective study. Issue 1 (December 2015) - Vollbach, Silke; Müller, Andreas; Drexler, Jan; Simon, Arne; Drosten, Christian; Eis-Hübinger, Anna; Panning, Marcus
Abstract Background Human enterovirus (EV) and parechovirus (HPeV) are significant causes of encephalitis and meningitis in children. The aim of this study was to determine the prevalence, type and viral RNA concentration of EV and HPeV in cerebrospinal fluid (CSF) samples in an unselected cohort of patients <18 years admitted to Bonn university hospital from 1998 to 2008. Methods A total of 327 CSF samples from 327 patients were retrospectively tested by real-time reverse-transcriptase PCR (RT-PCR) for EV and HPeV, and by real-time PCR for cytomegalovirus (CMV), herpes simplex virus 1/2 (HSV), and varizella zoster-virus (VZV). Samples had been submitted for routine virological work-up due to suspected meningitis or encephalitis and had been stored at −20 °C hereafter. Positive samples for EV and HPeV were sequenced within the gene encoding the VP1 region (EV), the VP2 and the VP3/VP1 junction region (HPeV). Results The overall prevalence was 4.3 % (14/327) for EV, 0.6 % (2/327) for HPeV, and 0.3 % (1/327) for HSV and VZV, respectively. CMV was not detected in this cohort. In children less than 3 months of age the prevalence was 7.7 % (2/26) for EV and 7.7 % (2/26) for HPeV, respectively. Frequency of EV detection ranged from 0 to 12 % per year and highest rates were observed from June to September. All typed EV belonged to species B. Both HPeV infections were detected in the fall of 2008 and were typed as HPeV genotype 3. Viral RNA concentrations were highest in patients with HPeV infection, followed by echovirus 30 and other EV. In total, 86 % (12/14) of EV infections presented as aseptic meningitis, whereas both HPeV infections presented as severe sepsis-like illness. Conclusions EV and HPeV were equally prevalent in children <3 months of age. Beyond the detection of EV and HPeV, the determination of viral RNA concentration and typing of EV and HPeV might prove beneficial for patient management and public health.